The teaching of Health of Worker in the undergraduate health courses of a federal university (Research, Society and Development, 2021)
Health of Worker raised important debates for the Brazilian Sanitary Reform, which implied new possibilities and challenges for the training of health professionals in Brazil, despite being a relatively new field. With this context in mind, this study sought to analyze the teaching of Health of Worker in undergraduate health courses at the Universidade Federal de Alagoas (Ufal). This is a qualitative, descriptive, documentary-based study. The Pedagogical Projects of the health courses at Ufal were analyzed. It was found that three of these courses have disciplines or modules related to Health of Worker. The little amplitude that the field in question has in health teaching may be associated with its little diffusion by the health network, figuring as specialized care, when it should be transversal to the system.